Anatomy of a disaster - overview of necrotising enterocolitis. - Meyer, H. (Professional Nursing Today, 2020)
When an infant is born prematurely, many of the body's systems are not quite developed enough to resist the onslaught of the world outside the womb. The gastrointestinal tract is just one of them. Despite many decades of research and clinical experience, necrotising enterocolitis (NEC) in the premature infant remains an enormous, often unexpected challenge from a diagnosis and treatment perspective, as well as the associated morbidity and mortality, as well as poor outcomes of survivors. Being aware of the risk factors can assist in earlier detection and possible avoidance of severe, surgical NEC as these infants have the worst outcomes. Implementing exclusive breast milk feeding protocols, avoidance of lower saturation targets, and supplementing the infant to enhance the robustness of the microbiome with probiotics are among the most valuable treatment algorithms currently evidenced in research.